Development of adsorbent for the simultaneous removal of organic and inorganic contaminants from aqueous solution - Choi, J. W.; Chung, S. G.; Hong, S. W.; Kim, D. J.; Lee, S. H. (IWA PUBLISHING, 2011)
In this study, a modified adsorbent, alginate complex beads, was prepared and applied to the removal of mixed contaminants from wastewater. The alginate complex beads were generated by the immobilization of powdered activated carbon and synthetic zeolites onto alginate gel beads, which were then dried at 110 degrees C for 20 h until the diameter had been reduced to 1 mm. This dry technique increased the hardness of the adsorbent to assure its durability and application. The adsorption onto the alginate complex beads of organic and inorganic compounds, as target contaminants, was investigated by performing both equilibrium and kinetic batch experiments. From the adsorption isotherms, according to the Langmuir equation, the alginate complex bead was capable of effectively removing benzene, toluene, zinc and cadmium. From kinetic batch experiments, the removal efficiencies of benzene, toluene, zinc and cadmium were found to be 66.5, 92.4, 74.1 and 76.7%, respectively, for initial solution concentrations of 100 mg L-1. The results indicated that the adsorbent developed in this study has the potential to be a promising material for the removal of mixed pollutants from industrial wastewater or contaminated groundwater.